Observational study to determine the pattern of distribution of stop - bang score in predicting OSA and its implication among female health care providers - G., Prabhu; Selvamuthukumaran, S.; S., Jayasri (International Journal of Medical Research and Review, 2019)
Objective: To determine the pattern of distribution of STOP-Bang score in predicting OSA and its implication among female health care providers. Methods: In this study, we enrolled 100 female health care providers with age>20 years and excluded subjects on long term respiratory illness and with secondary cause of obesity. Detailed historyand clinical examination were done along withfilled STOP-Bang questionnaire. Results: We included 100 subjects, the mean age was 26.23 ± 1.74 years, mean BMI was 23.18+ 1.73. Our study results, Snoring, Tiredness and observed apnea were observed more than other parameters. In the study, the significance of snoring (8% with ‘p’ value 0.006), tiredness (52% with ‘p’ value 0.000) and observed apnea (17% with ‘p’ value 0.001) was statistically significant.The most common score on the STOP-Bang questionnaire was 1point (n = 42), followed by no points (n = 41). Subjects with low risk were 57; with high risk were 2 which were statistically significant. Conclusion: Snoring, tiredness and observed apnea play an important factor among females in STOP-Bang score which also was statistically significant.The STOP-Bang questionnaire performed adequately for OSA screening in female health care providersindicated that it could be used as an effective non-invasive screening tool for identifying subjects with high risk of OSA.